Kajian Konsep Arsitektur Modern Pada Fasilitas Ruang Tunggu Stasiun Kereta Api Medan - Melly Andriana; Zuraidah Tharo; Novalinda (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Station is a place where trains depart and stop to serve boarding and disembarking passengers and/or loading and unloading goods and/or for train operation purposes. Railway Station is the main need needed in the procurement of train transportation modes. The station also has various functions that are part of its existence as a public facility. In addition to meeting the needs of the main function as a place for boarding or disembarking passengers and / or loading and unloading goods, at the station can be carried out supporting business activities for rail transportation such as shops, restaurants, offices, hotels (Law No. 13 of 1992). The method used is descriptive qualitative. The result of this research is in the form of a design in the waiting room at Medan Airport Railway Station. Planning is located on the 2nd floor of Medan Airport Railway Station. Planning and designing the commercial area at the station is carried out in order to have a positive impact on the local economy. Using modern Architecture concepts in the design in order to produce a simple room and and maximize the function of the purpose of the space created.